An Analysis of Rabies Incidence and Its Geographic Spread in the Buffer Area Among Orally Vaccinated Wildlife in Ukraine From 2012 to 2016 - Polupan, Ivan; Bezymennyi, Maksym; Gibaliuk, Yurii; Drozhzhe, Zhanna; Rudoi, Oleksii; Ukhovskyi, Vitalii; Nedosekov, Vitalii; De Nardi, Marco (Frontiers in Veterinary Science, 2019)
The statistics of rabies cases in Volyn, Lviv, and Zakarpattia oblasts of Ukraine from 2012 to 2016 were analyzed to establish spatial–temporal distribution of rabies endemic outbreaks and to identify causes of widespread infections among wild and domestic animals. The occurrence of rabies outbreaks in wild and domestic animals in Ukraine was also assessed to determine the effectiveness of oral rabies vaccination (ORV) efforts. According to our analysis, parenteral vaccination of domestic animals and ORV campaigns in foxes have proved unsuccessful in providing a sustainable, long-term reduction in endemic rabies outbreaks. ORV campaigns in foxes were deemed ineffective based on our studies of the endemic rabies outbreaks in Volyn, Lviv, and Zakarpattia oblasts in 2012–2016. The current rabies prevention system (parenteral vaccination) failed to offer protection to domestic animals based on our review of the occurrence of endemic rabies outbreaks in dogs and cats. ORV campaign shortcomings and their causes must be identified in order to provide maximum rabies vaccine coverage for dogs and cats. Altogether, the results presented here provide information that can assist public health agencies to devise more effective disease control plans to curtail the spread of rabies in domestic animals and wildlife in Ukraine.